Pengaruh Strategi Pemasaran Digital Terhadap Keputusan Pembelian Produk Di E-Commerce - Mirdad, Ade (Jurnal Bisnis Darmajaya, 2025)
The purpose of this study is to examine the influence of social media marketing, email marketing, and search engine marketing on the purchasing decision. This research used an online questionnaire where distributed to internet users over the age of 18 via G-form (Google Form). The sample used in this study amounted to 400 respondents. This study uses multiple linear regression method. The validity and reliability of the instrument were assessed using IBM SPSS. continued with the analysis of the classical assumption test, t-test and F-test. Partialy, Social Media Marketing and SEM have a positive and significant effect on Purchasing Decisions, but on the other hand the Email Marketing do not have a positive and significant effect on Purchasing Decisions.